Ecology without Us: Ecological Succession and History in Earth Abides. Issue 3 (January 2018) - Polefrone, Phillip R.
Abstract : George R. Stewart's Earth Abides (1949) is a classic American post-apocalypse novel, but it is also a thought experiment examining humanity's changing role on Earth that closely reflects the shift from a deterministic paradigm of ecological succession to one emphasizing contingency and human impact. Enmeshed in a community of scientists involved in the debate, Stewart creates a theory of environmentally embedded history in which human agency is understood as a partnership with the natural environment. By attending to Stewart's network of scientific influences, this article seeks to transcend the "antagonistic wilderness" reading of post-apocalyptic ecologies.